Microbial Diversity and Community Structure of Sulfate-Reducing and Sulfur-Oxidizing Bacteria in Sediment Cores from the East China Sea - Zhang, Yu; Wang, Xungong; Zhen, Yu; Mi, Tiezhu; He, Hui; Yu, Zhigang (Frontiers in Microbiology, 2017)
Sulfate-reducing bacteria (SRB) and sulfur-oxidizing bacteria (SOB) have been studied extensively in marine sediments due to their vital roles in both sulfur and carbon cycles, but the available information regarding the highly diverse SRB and SOB communities is not comprehensive. High-throughput sequencing of functional gene amplicons provides tremendous insight into the structure and functional potential of complex microbial communities. Here, we explored the community structure, diversity and abundance of SRB and SOB simultaneously through 16S rRNA, dsrB and soxB gene high-throughput sequencing and quantitative PCR analyses of core samples from the East China Sea. Overall, high-throughput sequencing of the dsrB and soxB genes achieved almost complete coverage (>99%) and revealed the high diversity, richness and OTU numbers of the SRB and SOB communities, which suggests the existence of an active sulfur cycle in the study area. Further analysis demonstrated that rare species make vital contributions to the high richness, diversity and OTU numbers obtained. Depth-based distributions of the dsrB, soxB and 16S rRNA gene abundances indicated that the SRB abundance might be more sensitive to the sedimentary dynamic environment than those of total bacteria and SOB. In addition, the results of unweighted pair group method with arithmetic mean (UPGMA) clustering analysis and redundancy analysis (RDA) revealed that environmental parameters, such as depth and dissolved inorganic nitrogen (DIN) concentrations, and the sedimentary dynamic environment, which differed between the two sampling stations, can significantly influence the community structures of total bacteria, SRB and SOB. This study provided more comprehensive information regarding the characteristics of SRB and SOB communities.